THE POSITION OF ACCOUNTING IN THE SMALL LIBERAL ARTS COLLEGE. - Hänslein, John D. (The Accounting Review, 1930)
Abstract In presenting the position in the small Liberal Arts College, it is necessary to distinguish between two groups of colleges. First, there is the group of colleges in which accounting has no place and second, there is that group of colleges in which accounting does have a place in the college curriculum. The evaluation of the practice of excluding any subject whatsoever that smacks of a vocational or business nature would lead to a discussion of the traditional ideas concerning what arts, sciences and humanities are justifiable in a college curriculum and what arts, sciences and humanities are not justifiable. The amount of attention given to the subject of Accounting and the establishment of its position in the small Liberal Arts College varies from very little, to making it the principal subject in the business course. Realizing the limitations of a one-semester course in accounting, some institutions give in the Department of Economics a full year's course. In order to give the student a still further knowledge and mastery of the subject of accounting, some of the smaller Liberal Arts Colleges provide for at least two years of accounting.